Qualify formative processes by promoting inclusive practices: the case of B. Pascal High school - Arianna Giuliani (Firenze University Press, 2022)
Promote inclusive processes by designing educational settings and activities seem to be confirmed as one of the most difficult challenges to which schools and teachers must respond. Encouraging the development, by all students, of engagement and skills useful for the future exercise of an active citizenship implies a broad commitment of teachers, as well as adequate mediation and co-planning skills of the specialized teacher. The contribution examines the results of a project conducted at the B. Pascal High school, based in Rome. Working with a class in which several students were supported by a specialized teacher, was focused the effectiveness that individual and small group reflection activities can have in enhancing communication and collaborative skills. The main evidence that emerged allow to highlight the effectiveness of the strategies used in promote an inclusive training experience.   Qualificare i processi formativi promuovendo pratiche inclusive: il caso dell'Istituto statale B. Pascal. Predisporre setting educativi e progettare la didattica in modo da promuovere processi inclusivi sembrano confermarsi tra le sfide più ardue a cui le scuole e gli insegnanti devono rispondere. Favorire lo sviluppo, da parte di tutti gli studenti, dell'engagement e di competenze utili per il futuro esercizio di una cittadinanza attiva implica un ampio impegno degli insegnanti, nonché una adeguata capacità di mediazione e co-progettazione dell'insegnante specializzato. Il contributo approfondisce gli esiti di un percorso progettuale condotto presso l'Istituto statale B. Pascal di Roma. Nel lavorare con una classe in cui erano presenti più studenti affiancati dall'insegnante specializzato, l'attenzione è stata posta sull'efficacia che attività di riflessione individuale e di piccolo gruppo possono avere nel potenziamento delle capacità comunicative e collaborative. Le evidenze emerse consentono di evidenziare l'efficacia delle strategie utilizzate rispetto alla possibilità di predisporre un'esperienza formativa inclusiva.